Cytological and cytomorphometric characteristics of buccal mucosa cells from smokeless tobacco users. Issue 11 (1st September 2017) - Dagli, Adile Ferda; Sahin, Nurhan; Bozdag, Zehra; Ucer, Ozlem; Akatli, Ayse Nur; Artas, Gokhan; Sahin, İbrahim and Yardim, Meltem and Dalkilic, Semih and Akkoc, Ramazan Fazil and Simsek, Sercan and Aydin, Suleyman
Abstract: Background: Use of smokeless tobacco (ST) is increasing in many communities. We investigated whether ST alters the cytological and cytomorphometric features of buccal mucosa cells. Methods: Twenty male participants who had used Nicotiana rustica Linn.‐containing ST (Maras powder) for at least 10 years, and 20 healthy male controls who did not use ST, were included in this study. After rinsing the mouth with water, samples were taken using a toothbrush from the buccal mucosa of subjects in both groups. Samples were gently spread over a glass slide. After applying a cytofixative spray, the Papanicolaou method was used to stain the slides. The presence of dysplasia, dyskeratosis, parakeratosis, hyperkeratosis, hypergranulosis, karyorrhexis, and pyknosis was evaluated by light microscopy, as were the increment amount of candida, cocco‐bacillus, and Leptotrichia buccalis . Cytomorphometric analysis was performed and at least 20 cells with well‐defined borders were evaluated from each slide, and the cellular diameter (CD), nuclear diameter (ND), and nucleus/cytoplasm (N/C) ratio of the cells were analyzed using a 60× objective. Results: Other than the presence of dysplasia and candida, all measured cytological parameters were significantly higher in the ST users than in the non‐ST users. Furthermore, CD was lower while nuclear/cytoplasmic ratio was higher in the ST users than in those non‐ST users. Conclusion: Cytological changes associated with the use of ST, include dyskeratosis, parakeratosis, hyperkeratosis, hypergranulosis, karyorrhexis, pyknosis together with increase in the bacterial population of cocco‐bacillus and L. buccalis . There were no significant differences in patients with dysplasia in spite of reduction of CD, increased nuclear size and N/C ratio.